1970
DOI: 10.1063/1.1673220
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Separation Effect on Gas and Isotope Mixtures Induced by Invasion of the Free Jet Shock Wave Structure

Abstract: The shock wave system of the underexpanded free jet, in a region where the pressure is in the range of 10−2 up to 1 torr, is partly invaded by background molecules, these latter being pumped and carried by the supersonic flow. When a gas mixture is introduced into the nozzle chamber and outside the shock barrel, this aspiration acts very selectively on the light molecules, and a mixture enriched in lighter species is attainable by skimming the free jet. This new aerodynamic separation effect, which is applicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

1973
1973
2006
2006

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 18 publications
3
27
0
1
Order By: Relevance
“…In the plasmas that are discussed in this paper, the ionization degree is 10% or even much less. The plasma expansion is then almost like that of a hot gas: [16][17][18][19][20] while expanding from the source, it accelerates and both the temperature and the density decrease. When the jet total pressure 21 approaches the background pressure, the flow goes through a stationary shock, after which the plasma expands subsonically.…”
Section: Rarefied Plasma Expansionmentioning
confidence: 99%
“…In the plasmas that are discussed in this paper, the ionization degree is 10% or even much less. The plasma expansion is then almost like that of a hot gas: [16][17][18][19][20] while expanding from the source, it accelerates and both the temperature and the density decrease. When the jet total pressure 21 approaches the background pressure, the flow goes through a stationary shock, after which the plasma expands subsonically.…”
Section: Rarefied Plasma Expansionmentioning
confidence: 99%
“…7͒ data it is concluded that the forward flux of H is not conserved over the shock region in the expansion of a thermal Ar-H plasma, which is a clear deviation of ''normal'' supersonic expansion behavior as described by supersonic expansion theory. [43][44][45] The in-depth physical discussion of the expansion properties of the plasma jet is left to a separate paper. 32,35 …”
Section: Velocity Measurementsmentioning
confidence: 99%
“…The diffusion of background gases into the isentropic expansion can result in signi®cant modi®cation of the mixed gas beam composition ratio, primarily favouring the lighter component. 34 As well, the placement or location of the skimmer can signi®cantly affect the composition of the beam which is ef®ciently transmitted into the second stage. 30 To avoid large deviations, the skimming should be performed well within the Mach disk.…”
Section: Resultsmentioning
confidence: 99%